Cold plasma treatment of porous scaffolds: Design principles. Issue 7 (20th May 2022) - Redzikultsava, Katazhyna; Baldry, Mark; Zhang, Anyu; Alavi, Seyedeh KH; Akhavan, Behnam; Bilek, Marcela M.
Abstract: Three‐dimensional porous scaffolds have the potential to revolutionize a number of fields, including stem cell research, biomedical implants, tissue engineering, and regeneration, as well as energy technologies, filtration, and sensing. The ability to precisely engineer their surface properties is paramount to successful and enduring application. Plasma treatments promise to deliver homogeneous surfaces with tailored characteristics while generating few by‐products and not relying on the diffusion of liquids into a porous network. However, forming plasma inside complex interconnected pores is a significant challenge and requires much parameter fine‐tuning. This study uses numerical modeling to investigate key parameters which affect plasma breakdown and makes practical recommendations for achieving treatment homogeneity. We consider a dielectric barrier discharge (DBD) system, where nitrogen gas flows through a glass tube containing a porous scaffold, which is surrounded by a cylindrical electrode, with ground electrodes at either end of the tube. The parameters investigated include the scaffolds' pore size and porosity as well as electrode size and position. The results showed that homogeneous treatment is achieved by avoiding alternative breakdown pathways such as a poor seal between the scaffold and the glass containment tube, using a narrow supply electrode centered at the scaffold, and positioning ground electrodes as close as possible to the supply electrode without arcing. This strategy maximizes the electric field strength at a given voltage, allowing for higher pressures to be used, which in turn give a more homogeneous mean free path inside the pores. Abstract : Experimental recommendations for achieving successful, homogeneous plasma treatment inside of complex 3D structures guided by a new, low resource‐requiring plasma modeling technique.